Association of Central Corneal Thickness with Intraocular Pressure - Mariam Zakia Chaudhari, Shahid Anwar Bhatti, Asma Zulfiqar, Uzma Najam, Aambreen Surti, Naseem Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Estimation of central corneal thickness is very important in the patients of glaucoma as it affects the intraocular pressure. Many studies have been done worldwide to find out the association of corneal thickness with the IOP but results are controversial. So the aim of current study was to find out the association of central corneal thickness with the intraocular pressure. Material and Methods: A cross sectional study was conducted in the outpatient department of ophthalmology, Kosher Fazal Teaching Hospital, Lahore during January 2022 to June 2022. Topical Proparacaine 0.5% was used to anesthetize the eye while 2% flourescene was applied to stain the cornea. IOP was measured by using Goldmann applanation tonometer while CCT was measured by ultrasonic pachymeter. Data was analyzed by using Statistical Package for Social Science (SPSS) version-20. Pearson correlation was used to find out the association of IOP with CCT. p-value of less than 0.05 was considered as significant. Results: Mean and standard deviation of age was 37.5 ± 4.9 with the range of 20 years up to 50 years. the central corneal thickness (CCT) of right eye was 531 ± 32.1 while that of left eye was 539 ± 30.9. The intraocular pressure (IOP) of right eye was 15.3 ± 2.7 and left eye was 15.9 ± 3.4. Pearson correlation coefficient found a strong significant association between central corneal thickness and intraocular pressure in both eyes with p-value ≤0.05. Conclusion: It can be concluded that central corneal thickness is significantly associated with intraocular pressure so there is a need to modify the protocol by adding measurement of central corneal thickness before measuring intraocular pressure. Keywords: Central corneal thickness, Intraocular pressure, Glaucoma